Introduction to Digital Scholarship - Zeffiro, Andrea (My University, 2017)
What is digital scholarship and how can I do more with it? This workshop introduces participants to the interdisciplinary and multi-modal sphere of digital scholarship. We will briefly explore the facets of digital scholarly research and dissemination, and spend the bulk of our time authoring digital scholarship research plans.
Keywords: Digital scholarship; research design